107 Eating Disorder Symptoms as a Risk Factor for Hypoactive Sexual Desire Disorder in Women: A Pilot-Study. (1st May 2022) - Cipriani, S; Maseroli, E; Stasi, V Di; Scavello, I; Paoletti, C; Castellini, G; Ricca, V; Maggi, M; Vignozzi, L
ABSTRACT: Introduction: Eating and sexual behavior are driven by neurological mechanisms that are extremely intertwined; emerging evidence indicates that their deep relationship can be mediated by the presence of specific psychopathologies. Objective: to investigate the relationship between female sexual dysfunction (FSD) and eating disorders (EDs). Methods: 123 retrospectively recruited women consulting for FSD underwent physical examination and completed the following validated questionnaires: Female Sexual Function Index (FSFI), Female Sexual Distress Scale-Revised (FSDS-R), Eating Disorder Examination Questionnaire (EDE-Q), Binge Eating Scale (BES), Emotional Eating Scale (EES), Barrat Impulsiveness Scale-11 (BIS-11), Beck Depression Inventory (BDI), State-Trait Anxiety Inventory Y (STAI Y), Symptom Checklist 90-Revised (SCL-90-R), Body Uneasiness Test (BUT), Dyadic Adjustment Scale (DAS) and Sexual Inhibition/Sexual Excitation Scales (SIS/SES). Moreover, demographic, medical and psycho-sexuological data were obtained through a structured interview. Results: in relation to menopausal status, we did not observe any significant difference in all the investigated questionnaires in pre- vs. post-menopausal women. When stratifying patients for BMI (<25, 25-30, >30 kg/m2) we found that all the scores related to EDE-Q subscales were significantly different among the three subgroups (all p<0.001). Furthermore, patients with a history of Unwanted Sexual Experience (USE) had significantly higher BES (p=0.034) and EES (p=0.027) total scores compared with those without. Moreover, when we stratified our patients according to the clinical diagnosis of Hypoactive Sexual Desire Disorder (HSDD), we found that those with HSDD showed a worst psychological profile than those without, in particular a higher score at EDE-Q and BDI (all p<0.05). In contrast, when stratifying patients for the other two main FSD diagnosis, Female Genital Arousal Disorder (FGAD) and Female Orgasm Disorder (FOD), no significant differences among all the investigated questionnaires were observed. To further verify the impact of the different psychopathological aspects on the risk of having HSDD, we found that the only questionnaires scores that contributed to this dysfunction were EDE-Q (OR 1.678, IC [1.164-2.421]; p=0.006), total BDI (OR 1.055, IC [1.006-1.107]; p=0.027) and SIS1 (OR 1.101, IC [1.109-1.190]; p=0.015), after adjustment for age (Fig. 1). After simultaneous analysis in a multivariate model of the three questionnaires, we found that both a higher EDE-Q score and a higher SIS1 score were significant risk factors for HSDD (p=0.007 and p=0.034, respectively). Finally, we subdivided our patients into three groups: no Binge Eating (BE), sporadic BE and frequent BE, observing a significant positive association between frequency of BE and sexual distress, as assessed by FSDS-R total score (Fig. 2). Conclusions: in a population of women affected by FSD, ED traits could negatively affect sexual desire, representing a relevant risk factor for the clinical diagnosis of HSDD. Among all the investigated psychopathological aspects, the psychological alterations related to EDs seem to play a more pronounced effect on HSDD than other commonly accepted risk factors for sexual desire disorders, such as depression and increased inhibitory trait. In a clinical perspective, it would worth to investigate the relative change in FSD and ED after treatment for ED and vice versa . Disclosure: Work supported by industry: no.